Role of Education and Pedagogical Approach in Service Learning - Sengupta, Enakshi; Blessinger, Patrick (Bingley, UK : Emerald Publishing Limited, 2023)
Role of Education and Pedagogical Approach in Service Learnings a collection of case studies and interventions adopted by academics across the globe to explain and explore the concepts of social responsibility in education, social justice and civility.
Includes bibliographical references and indexes.
Keywords: Service learning; Web-based instruction; Student volunteers in social service